The Changes of Functional Connectivity Strength in Electroconvulsive Therapy for Depression: A Longitudinal Study - Wei, Qiang; Bai, Tongjian; Chen, Yang; Ji, Gongjun; Hu, Xiaopeng; Xie, Wen; Xiong, Zulun; Zhu, Daomin; Wei, Lin; Hu, Panpan; Yu, Yongqiang; Wang, Kai; et al. (Frontiers in Neuroscience, 2018)
Electroconvulsive therapy (ECT) is an effective treatment for depression, but the mechanism of ECT for depression is still unclear. Recently, neuroimaging studies have reported that the prefrontal cortex, hippocampus, angular gyrus, insular and other brain regions are involved in the mechanism of ECT for depression, and these regions are highly overlapped with the location of brain hubs. Here, we try to explore the effects of ECT on the functional connectivity of brain hubs in depression patients. In current study, depression patients were assessed at three time points: prior to ECT, at the completion of ECT and about 1 month after the completion of ECT. At each time point, resting-state functional magnetic resonance imaging, assessment of clinical symptoms and cognition function were performed respectively, which was compared with 20 normal controls. Functional connectivity strength (FCS) was used to identify brain hubs. The results showed that FCS of left angular gyrus in depression patients significantly increased after ECT, accompanied by improved mood. The changed FCS in depression patients recovered obviously at 1 month after the completion of ECT. It suggested that ECT could modulate functional connectivity of left angular gyrus in depression patients.